Forests and Forestry in Mizoram - a Profile - Savant, P. V.; Patnalk, S. S. (Indian Forester, 1998)
The Mizoram is primarily a Tribal State. Agriculture is the mainstay of the people. Traditional 'Jhum' is practiced. The forests of the State broadly classified into (1) Tropical Wet Evergreen, (2) Tropical Semi-Evergreen and (3) Montane Sub-Tropical Pine forests. Past and present Forest Management System, Afforestation Programme, Farm Forestry, Wildlife Management, Biodiversity Conservation, Forest Research and Training, Joint Forest Management have been discussed.